2022
DOI: 10.1177/21501319221112585
|View full text |Cite
|
Sign up to set email alerts
|

Responding to COVID-19 While Serving Veterans Experiencing Homelessness: The Pandemic Experiences of Healthcare and Housing Providers

Abstract: The U.S. Department of Veterans Affairs (VA) provides essential care through transitional housing and healthcare for Veterans experiencing homelessness through the Grant and Per Diem (GPD) program and the Homeless Patient Aligned Care Team (HPACT), respectively. At the onset of the SARS-CoV-2 pandemic, GPD organizations and HPACT clinics faced the challenge of being essential providers tasked with ensuring the well-being of Veterans under their care. Through semi-structured interviews with 13 providers (6 HPAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Bivariate comparative analyses were conducted to assess potential differences between the SMI and non-SMI patient groups, as well as between those with primary diagnoses of schizophrenia, bipolar disorder, or non-SMI on a number of characteristics evaluated in prior research. These characteristics include demographics (age, gender, race, ethnicity, marital status, urban or rural status; Cuadros et al, 2021 ; Tzur Bitan et al, 2021 ), medical (Elixhauser count; Elixhauser et al, 1998 ) and psychiatric (post-traumatic stress disorder [PTSD], substance use disorder [SUD]) comorbidities ( Li et al, 2020 ), specific VHA factors (military service connected disability rating, behavioral risk flag, suicide risk flag; Krishnamurti et al, 2022 ), homelessness ( Gin et al, 2022 ), and service utilization (primary care and mental health care encounters; Ferguson et al, 2021 ). Stepwise logistic regression analyses were used to evaluate the incremental contribution of variables on mortality risk.…”
Section: Methodsmentioning
confidence: 99%
“…Bivariate comparative analyses were conducted to assess potential differences between the SMI and non-SMI patient groups, as well as between those with primary diagnoses of schizophrenia, bipolar disorder, or non-SMI on a number of characteristics evaluated in prior research. These characteristics include demographics (age, gender, race, ethnicity, marital status, urban or rural status; Cuadros et al, 2021 ; Tzur Bitan et al, 2021 ), medical (Elixhauser count; Elixhauser et al, 1998 ) and psychiatric (post-traumatic stress disorder [PTSD], substance use disorder [SUD]) comorbidities ( Li et al, 2020 ), specific VHA factors (military service connected disability rating, behavioral risk flag, suicide risk flag; Krishnamurti et al, 2022 ), homelessness ( Gin et al, 2022 ), and service utilization (primary care and mental health care encounters; Ferguson et al, 2021 ). Stepwise logistic regression analyses were used to evaluate the incremental contribution of variables on mortality risk.…”
Section: Methodsmentioning
confidence: 99%
“…The research team also interviewed staff at all seven GPD organizations to inquire about their experiences providing care during COVID-19 and what they were doing to facilitate Veterans’ vaccination. Staff perspectives are reported elsewhere [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, for clients with very specific and complex health needs, in-person or in-field services were provided when necessary (e.g., administration of non-oral medicine, renewal or signing of tenant contracts, delivery of food goods); however such services were not continuous but rather implemented as needed. Other studies reported similar response strategies implemented by homeless-serving organizations in other high-income settings, such as in the United Kingdom [ 46 , 51 ] and the USA [ 52 ]. Our study and others provide evidence of the critical role that community-based organizations, their frontline workers [ 45 ], and successful partnerships with the private sector [ 53 , 54 ] and other agencies [ 55 ] have in innovating and quickly adapting support services to respond to the needs of underserved or socially excluded populations during public health emergencies.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, alongside increasing coordination, integration, and collaboration across social and health support services, our study participants recommended that more specialized mental health services (including substance use and harm reduction) and health and social support professionals (well-paid and cared supportive workforce) along with more personalized socioeconomic supports are required to strengthen and improve the support responses for underserved populations during and beyond pandemics. Lessons learned from the COVID-19 pandemic should support allocating and investing additional (financial, material and personnel) resources across social, health and housing systems to ensure a more inclusive, equitable, sustainable and innovative post-pandemic recovery plan for socio-economically excluded and underserved populations [52,55,72,[74][75][76][77][78].…”
Section: Plos Onementioning
confidence: 99%